2016
DOI: 10.1038/srep33840
|View full text |Cite
|
Sign up to set email alerts
|

Engineering new balancer chromosomes in C. elegans via CRISPR/Cas9

Abstract: Balancer chromosomes are convenient tools used to maintain lethal mutations in heterozygotes. We established a method for engineering new balancers in C. elegans by using the CRISPR/Cas9 system in a non-homologous end-joining mutant. Our studies will make it easier for researchers to maintain lethal mutations and should provide a path for the development of a system that generates rearrangements at specific sites of interest to model and analyse the mechanisms of action of genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 29 publications
1
54
0
Order By: Relevance
“…Two DSBs have been used to make chromosomal rearrangements, including inversions translocations, and large deletions (Blasco et al 2014;Chen et al 2014;Choi and Meyerson 2014;Ghezraoui et al 2014;Maddalo et al 2014;Paix et al 2014;Iwata et al 2016;Dejima et al 2018). We found that adding a second DSB at a distance of 340 bp from the initial DSB ( Figures 5A and S2) This double DSB strategy also worked well using a variety of linear and circular doublestranded repair templates with 500 bp homology arms to insert fluorescent reporters: 21% dpy-10 mutants had precise insertions of 8221 bp, 17% had precise insertions of 5060 bp, and 36% had precise insertions of 2138 bp ( Figure 5B).…”
Section: Efficient Strategies To Insert Large Dna Fragments At Wide-rmentioning
confidence: 99%
“…Two DSBs have been used to make chromosomal rearrangements, including inversions translocations, and large deletions (Blasco et al 2014;Chen et al 2014;Choi and Meyerson 2014;Ghezraoui et al 2014;Maddalo et al 2014;Paix et al 2014;Iwata et al 2016;Dejima et al 2018). We found that adding a second DSB at a distance of 340 bp from the initial DSB ( Figures 5A and S2) This double DSB strategy also worked well using a variety of linear and circular doublestranded repair templates with 500 bp homology arms to insert fluorescent reporters: 21% dpy-10 mutants had precise insertions of 8221 bp, 17% had precise insertions of 5060 bp, and 36% had precise insertions of 2138 bp ( Figure 5B).…”
Section: Efficient Strategies To Insert Large Dna Fragments At Wide-rmentioning
confidence: 99%
“…GRIBCG is a fast and easy-to-use tool for the selection of sgRNAs in the rational design of balancer chromosomes. While previous work has demonstrated successful generation of balanced regions in C. elegans and Danio rerio [5,7], our tool is the first designed to create a completely balanced chromosome with the use of a single sgRNA. Experimentally, using a single sgRNA would eliminate the need for multiple rounds of transformation, and decrease the number of generations that need to be screened in order to identify a completely balanced chromosome.…”
Section: Resultsmentioning
confidence: 99%
“…In plant breeding, balancer chromosomes could help preserve the advantages of heterosis without full apomixis [4]. CRISPR/Cas9 genome editing can generate inverted regions similar to the rearrangements present in balancer chromosomes ( Figure 1) [5,6]. Chromosomal rearrangements have been reported in C. elegans and zebrafish germlines, and in pig, mouse, and human somatic cells [5,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of using CRISPR/Cas9 to engineer chromosome rearrangements in other model systems include the creation of an oncogenic translocation in mice (5), translocations in yeast (6), translocations and inversions in C. elegans (7,8), and inversions in zebrafish (9). This study represents the first report of a chromosomal rearrangement induced by CRISPR/Cas9 in the Drosophila germline.…”
Section: Introductionmentioning
confidence: 91%